2021
DOI: 10.1302/0301-620x.103b3.bjj-2020-1288.r1
|View full text |Cite
|
Sign up to set email alerts
|

Single dose of tranexamic acid effectively reduces blood loss and transfusion rates in elderly patients undergoing surgery for hip fracture: a randomized controlled trial

Abstract: Aims The aim of this study was to investigate the hypothesis that a single dose of tranexamic acid (TXA) would reduce blood loss and transfusion rates in elderly patients undergoing surgery for a subcapital or intertrochanteric (IT) fracture of the hip. Methods In this single-centre, randomized controlled trial, elderly patients undergoing surgery for a hip fracture, either hemiarthroplasty for a subcapital fracture or intramedullary nailing for an IT fracture, were screened for inclusion. Patients were random… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 38 publications
2
24
3
Order By: Relevance
“…In this study, the rate of blood transfusion was 10.46% (95% CI : 8.23–13.21), which was lower than report of Nikolaou et al (63.47%) [ 6 ], Ohmori et al (32.67%) [ 33 ], and Guo et al (29.7%) [ 5 ] in hip fracture patients. The reason might be that the blood loss continue until several days after surgery [ 9 ], but this study only analyzed the blood transfusions from admission to the time of blood routine test.…”
Section: Discussioncontrasting
confidence: 70%
See 2 more Smart Citations
“…In this study, the rate of blood transfusion was 10.46% (95% CI : 8.23–13.21), which was lower than report of Nikolaou et al (63.47%) [ 6 ], Ohmori et al (32.67%) [ 33 ], and Guo et al (29.7%) [ 5 ] in hip fracture patients. The reason might be that the blood loss continue until several days after surgery [ 9 ], but this study only analyzed the blood transfusions from admission to the time of blood routine test.…”
Section: Discussioncontrasting
confidence: 70%
“…Even more, it is estimated that there will be 4.5 million hip fractures worldwide by the year 2050, and 1.3 million cases will be in China [ 3 , 4 ]. After the initial injury, hip fracture patients may suffer from a large amount of total blood loss, which vary from 859 ml to 1208 ml in patients with femur neck fracture [ 5 7 ], and 406 ml to 1269 ml in patients with intertrochanteric fracture [ 6 , 8 11 ]. Similarly, a prospective study found that the blood loss can reach up to 1013 ml even prior to the surgery [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients in the training set were used to develop the nomogram model, whereas patients in the testing set were used to validate the resulting nomogram. The use of TXA involved a single dose of intravenous TXA (15 mg/kg) 30 min prior to surgery in the study [ 10 ]. According to the World Health Organization criteria, the degree of anemia was classified as mild (male, 11-12.9 g/dl; female, 11-11.9 g/dl), moderate (8-10.9 g/dl), or severe (< 8 g/dl) [ 11 ].…”
Section: Methodsmentioning
confidence: 99%
“…A similar tendency was identified in patients undergoing hemiarthroplasty for a subcapital fracture but not to a statistically significant level. [ 21 ] We first reported the effects of topical application of TXA in intertrochanteric fracture patients with PFNA. Our data showed that the TBL was reduced by 30% (from 813–566 mL) and the HBL was reduced by 31% (from 652–447 mL) after topical treatment with TXA during surgery.…”
Section: Discussionmentioning
confidence: 99%